2005
DOI: 10.1002/jsfa.2117
|View full text |Cite
|
Sign up to set email alerts
|

In vivo determination of fat content in Atlantic salmon (Salmo salar) with a mobile NMR spectrometer

Abstract: A new method for the rapid measurement of the fat content in live (or slaughtered) Atlantic salmon, based on a mobile low-field NMR analyser, has been developed and tested. The instrument, calibrated against a set of reference samples (fish oil in agarose), was used for non-destructive fat determination of the Norwegian quality cut (NQC) of anaesthetized fish. The total analysis time per fish was about 20 s. The fat content (range 90-182 g kg −1 ) showed significant correlation (r = 0.92) with chemical extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…It is also an important factor in consumer acceptance (Probert and Shannon, 2000;Romvári et al ., 2002;Veliyulin et al ., 2005). Traditionally, carcass composition in fish was determined by comparative slaughtering followed by chemical analysis (Oberle et al ., 1997).…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also an important factor in consumer acceptance (Probert and Shannon, 2000;Romvári et al ., 2002;Veliyulin et al ., 2005). Traditionally, carcass composition in fish was determined by comparative slaughtering followed by chemical analysis (Oberle et al ., 1997).…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
“…Other methods such as ultrasound velocity (Suvanich et al ., 1998;Sigfusson et al ., 2000) or near-infrared techniques (Wold and Isaksson, 1997) are based on fillet samples or dead fish. However, fish production is heavily dependent on quick, accurate and, above all, non-invasive methods to predict carcass composition in live fish (Probert and Shannon, 2000;Veliyulin et al ., 2005;Silva et al ., 2010a). Comprehensive studies using image techniques such as CT (Romvári et al ., 2002;Hancz et al ., 2003;Kolstad et al ., 2004), MRI (Collewet et al ., 2001;Veliyulin et al ., 2005) and RTU (Bosworth et al ., 2001;Rodrigues et al ., 2010;Silva et al ., 2010a) have shown that these techniques are able to predict carcass traits in fish.…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The same unilateral NMR device was tested by Veliyulin et al [43] to set up rapid non-destructive measurement of the fat content in live or slaughtered Atlantic salmon. The total analysis time per fish was about 20 s. The distribution of transverse relaxation times when measured with a conventional benchtop NMR instrument shows three peaks.…”
Section: Application Of Single-sided Nmr Sensors To Food Matricesmentioning
confidence: 99%
“…5 A number of interesting applications have been demonstrated, including determination of fat content in live Atlantic salmon, 6 one-dimensional imaging of heterogeneous rubbers, 7 characterisation of polymer materials, 8 self-diffusion measurements, 9 tendon anisotropy studies 10 and detection of water ingress in model aerospace composites. 11 Unilateral NMR has other advantages over a traditional benchtop time domain NMR.…”
Section: Introductionmentioning
confidence: 99%